Unsupervised domain adaptation for the segmentation of breast tissue in mammography images. (November 2021) - Ryan, Frances; Román, Karen López-Linares; Gerbolés, Blanca Zufiria; Rebescher, Kristin May; Txurio, Maialen Stephens; Ugarte, Rodrigo Cilla; González, María Jesús García; Oliver, Iván Macía
Highlights: We demonstrate the effectiveness of adversarial-based UDA for breast tissue segmentation, which has not been shown before. We show how reconstruction and adversarial methods can be combined to perform training with single-source-multiple-target domains, contributing further work to the less-commonly addressed problem of domain adaptation with more than one target. Abstract: Background and Objective: Breast density refers to the proportion of glandular and fatty tissue in the breast and is recognized as a useful factor assessing breast cancer risk. Moreover, the segmentation of the high-density glandular tissue from mammograms can assist medical professionals visualizing and localizing areas that may require additional attention. Developing robust methods to segment breast tissues is challenging due to the variations in mammographic acquisition systems and protocols. Deep learning methods are effective in medical image segmentation but they often require large quantities of labelled data. Unsupervised domain adaptation is an area of research that employs unlabelled data to improve model performance on variations of samples derived from different sources. Methods: First, a U-Net architecture was used to perform segmentation of the fatty and glandular tissues with labelled data from a single acquisition device. Then, adversarial-based unsupervised domain adaptation methods were used to incorporate single unlabelled target domains, consisting of images from a different machine, into the training. Finally, the domain adaptation model was extended to include multiple unlabelled target domains by combining a reconstruction task with adversarial training. Results: The adversarial training was found to improve the generalization of the initial model on new domain data, demonstrating clearly improved segmentation of the breast tissues. For training with multiple unlabelled domains, combining a reconstruction task with adversarial training improved the stability of the training and yielded adequate segmentation results across all domains with a single model. Conclusions: Results demonstrated the potential for adversarial-based domain adaptation with U-Net architectures for segmentation of breast tissue in mammograms coming from several devices and demonstrated that domain-adapted models could achieve a similar agreement with manual segmentations. It has also been found that combining adversarial and reconstruction-based methods can provide a simple and effective solution for training with multiple unlabelled target domains.